2021
DOI: 10.1177/0894845321991680
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Barriers, Expected Outcomes, and Practices in Scientific Communication: Scale Development and Validation

Abstract: Developing new scales to measure aspects of mentoring, including guidance in scientific communication (SciComm), is important to enhance success among trainees pursuing research careers in science and medicine. This study examined the psychometric properties of three new measures, based on social cognitive career theory (SCCT), as mentors address skills in scientific writing, oral presentation, and impromptu speaking. Faculty research mentors ( N = 194) completed online questionnaires assessing perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Barriers to mentoring in SciComm. Perceived barriers to mentoring trainees in SciComm were measured with a 22-item scale assessing trainee, institutional, and mentor-self barriers (Anderson et al, 2020). Trainee barriers (9 items) represent contextual influences that SCCT proposes relate to choice actions directly or indirectly through self-efficacy, that is, trainee issues that make it difficult for mentors to help trainees with SciComm tasks (e.g., trainee weakness in basic English writing skills, insufficient effort, dread of negative feedback or criticism).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Barriers to mentoring in SciComm. Perceived barriers to mentoring trainees in SciComm were measured with a 22-item scale assessing trainee, institutional, and mentor-self barriers (Anderson et al, 2020). Trainee barriers (9 items) represent contextual influences that SCCT proposes relate to choice actions directly or indirectly through self-efficacy, that is, trainee issues that make it difficult for mentors to help trainees with SciComm tasks (e.g., trainee weakness in basic English writing skills, insufficient effort, dread of negative feedback or criticism).…”
Section: Methodsmentioning
confidence: 99%
“…This scale measures positive outcomes (6 items; e.g., "My own productivity is increased by mentoring") and negative outcomes (7 items; e.g., "Mentoring takes valuable time away from my own tasks") on a 5-point Likert-type scale ranging from 1 (strongly disagree) to 5 (strongly agree). Anderson et al (2020) reported Cronbach's a reliabilities of .69 for positive and .81 for negative expected outcomes from mentoring. Only 2 positive and 3 negative items were measured in both Sample 1 and Sample 2, so 5 expected outcomes items were included in the combined analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Se han identificado tres tipos principales de barreras a la mentoría que surgen de las personas mentoras, las que reciben mentoría y de las instituciones (Anderson, 2021;Serrano-García, 2015;Veeramah, 2012). Para las personas mentoras, las barreras principales son: (a) desconocimiento de la tarea y sus beneficios, (b) características de personalidad y valores incompatibles con las funciones y (c) dificultades para evaluar el resultado de la relación.…”
Section: Desarrollo Profesionalunclassified